PERAN PEMBELAJARAN BAHASA JERMAN DALAM MEMBENTUK SIKAP TOLERANSI SEBAGAI KARAKTER WARGA NEGARA GLOBAL - Cahya Maulidia; Erlangga Hikmah Budhyatma (Fakultas Keguruan dan Ilmu Pendidikan Program Studi Pendidikan Pancasila dan Kewarganegaraan, 2026)
In the era of globalization, interactions among individuals from different countries and cultural backgrounds are increasing. This is influenced by the rapid development of technology, which enables individuals to communicate more easily without limitations of distance or time. These conditions require the presence of tolerance as part of the character of global citizens. Foreign language learning, particularly German, not only functions as a means of communication in international contexts but also as a medium for enhancing understanding of the culture and values of German society. By understanding the language, learners are able to comprehend the perspectives, habits, and value systems of a society, thereby encouraging the growth of mutual respect among cultures. This study aims to analyze the role of German language learning in fostering tolerance as part of the character of global citizens. The method used is a literature review by examining various scientific sources. The results of the study indicate that German language learning plays a role in improving intercultural understanding, which in turn promotes the development of tolerance.